Long-term trend and fluctuations of karst spring discharge in a Mediterranean area (central-southern Italy) - Fiorillo F.; Petitta M.; Preziosi E; RUSI, Sergio; Esposito L.; Tallini M. (Environmental Earth Sciences, 2015)
Karst springs in central-southern Italy are largely exploited for the human consumption since the Roman Times and currently feed some tens of millions inhabitants with tap water of high quality. Unlike other karst springs, they are characterized by a steady rate during the year with modest seasonal variability. However, the effects of climate changes are being strongly perceived in central and southern Italy as in the rest of the Mediterranean basin, and groundwater is obviously also affected. In this paper, we analyze the discharge time series of some important karst springs in the region, evaluating the trends and fluctuations in relation to rainfall regime, on a yearly time scale. The aim is to evaluate the response of these large karst aquifers in the Mediterranean area to the recharge input variation. The role of the North Atlantic Oscillation has also been considered. Trends and fluctuations have been highlighted by n-years moving average and transforming the time series by the Rescaled Adjusted Partial Sum. The results show that a drop in the discharge has occurred since 1987, with reductions ranging from 15 up to 30 %, although this negative trend is now possibly attenuating or even reversing. As a final remark, the spring discharge of the large karst aquifers in central-southern Italy can be assumed as a robust indicator for climate changes as it integrates the effects of precipitation and temperature variation in time and space. © 2014, Springer-Verlag Berlin Heidelberg.